2021
DOI: 10.1186/s13643-021-01589-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-primary progressive language impairment in neurodegenerative conditions: protocol for a scoping review

Abstract: Background Progressive language difficulties arise in many neurodegenerative conditions, causing significant impact upon patients and families. This occurs most obviously in primary progressive aphasia (PPA) but can also occur within other forms of progressive disease. In these cases, language decline may be significant, but as they are not the presenting or dominant symptom, may be overlooked in favour of more prominent cognitive, behaviour or motor deficits. To date, there has been no systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The specific electronic search strategy can be found in the study protocol published by Savage et al 13 . The search for PubMed comprised the following terms: (Early‐onset Alzheimer's disease OR early onset Alzheimer's disease OR young‐onset Alzheimer's disease OR young onset Alzheimer's disease OR Parkinson* dementia OR Parkinson* disease dementia OR dementia with Lewy bodies OR Lewy body dementia OR Posterior Cortical Atrophy OR frontotemporal dementia OR Pick's disease OR Progressive Supranuclear Palsy OR Cortico‐basal Syndrome OR cortico‐basal degeneration OR corticobasal degeneration OR motor neuron disease OR FTD‐MND OR MND‐FTD OR ALS‐FTD OR FTD‐ALS) AND (language impairment OR communication disorder OR aphasia).…”
Section: Methods and Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific electronic search strategy can be found in the study protocol published by Savage et al 13 . The search for PubMed comprised the following terms: (Early‐onset Alzheimer's disease OR early onset Alzheimer's disease OR young‐onset Alzheimer's disease OR young onset Alzheimer's disease OR Parkinson* dementia OR Parkinson* disease dementia OR dementia with Lewy bodies OR Lewy body dementia OR Posterior Cortical Atrophy OR frontotemporal dementia OR Pick's disease OR Progressive Supranuclear Palsy OR Cortico‐basal Syndrome OR cortico‐basal degeneration OR corticobasal degeneration OR motor neuron disease OR FTD‐MND OR MND‐FTD OR ALS‐FTD OR FTD‐ALS) AND (language impairment OR communication disorder OR aphasia).…”
Section: Methods and Designmentioning
confidence: 99%
“…A protocol of this scoping review can be found in a previous publication 13 . The protocol followed the Preferred Reporting Items for Systematic Reviews and Meta‐analysis Protocols (PRISMA)‐ScR guidelines 14,15 .…”
Section: Methods and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same line, the diagnostic criteria for SLDs in progressive supranuclear palsy (PSP) incorporate non-fluent/agrammatic primary progressive aphasia and progressive apraxia of speech (Boxer et al, 2017;Höglinger et al, 2017), yet overlooked alternate language phenotypes [e.g., dynamic aphasia (DA) and echolalia], which can also herald the onset of PSP (Ghika et al, 1995;Esmonde et al, 1996;Della Sala and Spinnler, 1998;Robinson et al, 2006Robinson et al, , 2015Rohrer et al, 2010;Perez et al, 2013;Fernández-Pajarín et al, 2015;Magdalinou et al, 2018). Therefore, it is essential to further delineate the broad spectrum of SLDs in PSP (Catricalà et al, 2019;Peterson et al, 2019) and in other degenerative non-PPA conditions (see Savage et al, 2021). In fact, the language profile of DA (specific deficits in the generation of novel verbal messages) (Luria and Tsvetkova, 1967) in PSP has been clearly delineated (Robinson et al, 2006(Robinson et al, , 2015, yet less well known is its relationship with concurrent echolalia (repetition of what has been heard) (e.g., Della Sala and Spinnler, 1998;Berthier et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%